Body mass index and outcome after revascularization for symptomatic carotid artery stenosis. (23rd May 2017) - Volkers, Eline J.; Greving, Jacoba P.; Hendrikse, Jeroen; Algra, Ale; Kappelle, L. Jaap; Becquemin, Jean-Pierre; Bonati, Leo H.; Brott, Thomas G.; Bulbulia, Richard; Calvet, David; Eckstein, Hans-Henning; Fraedrich, Gustav; et al.
Abstract : Objective: To determine whether the obesity paradox exists in patients who undergo carotid artery stenting (CAS) or carotid endarterectomy (CEA) for symptomatic carotid artery stenosis. Methods: We combined individual patient data from 2 randomized trials (Endarterectomy vs Angioplasty in Patients with Symptomatic Severe Carotid Stenosis and Stent-Protected Angioplasty vs Carotid Endarterectomy) and 3 centers in a third trial (International Carotid Stenting Study). Baseline body mass index (BMI) was available for 1, 969 patients and classified into 4 groups: <20, 20–<25, 25–<30, and ≥30 kg/m 2 . Primary outcome was stroke or death, investigated separately for the periprocedural and postprocedural period (⩽120 days/>120 days after randomization). This outcome was compared between different BMI strata in CAS and CEA patients separately, and in the total group. We performed intention-to-treat multivariable Cox regression analyses. Results: Median follow-up was 2.0 years. Stroke or death occurred in 159 patients in the periprocedural (cumulative risk 8.1%) and in 270 patients in the postprocedural period (rate 4.8/100 person-years). BMI did not affect periprocedural risk of stroke or death for patients assigned to CAS ( p trend = 0.39) or CEA ( p trend = 0.77) or for the total group ( p trend = 0.48). Within the total group, patients with BMI 25–<30 had lower postprocedural risk of stroke or death than patients with BMI 20–<25 (BMI 25–<30 vs BMI 20–<25; hazard ratio 0.72; 95% confidence interval 0.55–0.94). Conclusions: BMI is not associated with periprocedural risk of stroke or death; however, BMI 25–<30 is associated with lower postprocedural risk than BMI 20–<25. These observations were similar for CAS and CEA.